Connection between nutrition and oncology in dogs and cats: perspectives, evidence, and implications—a comprehensive review - Amaral, Andressa R.; Finardi, Gabriela L. F.; Marchi, Pedro H.; de Oliveira, Natália M. C.; Príncipe, Leonardo A.; Teixeira, Natacha; Pappalardo, Maria C. F.; Lima, Laís O. C.; Cirillo, Juliana V.; Balieiro, Júlio Cesar de C.; Vendramini, Thiago H. A. (Frontiers in Veterinary Science, 2025)
Oncology has become one of the most influential and studied areas in both human and companion animal health. In veterinary practice, cancer represents a significant challenge, especially concerning cats and dogs. Nutrition plays a crucial role in the management of oncology patients in veterinary medicine; however, is often nonspecific and reliant on data from other species and diseases, highlighting the need for a comprehensive review of the latest developments in this field. Since the intricate relationship between nutrition and cancer encompasses various aspects, this review therefore intends to cover the most important points in nutrition in canine and feline oncology. Therefore, topics are addressed that include discussion about the effects of cancer on nutrition, cancer-related cachexia, the influence of obesity on both the occurrence and progression of cancer, essential nutrients for oncologic patients, and nutritional supplementation.